Increased platelet-to-lymphocytes ratio is associated with poor long-term prognosis in patients with pancreatic cancer after surgery. Issue 25 (June 2018) - Yu, Jinming; Ding, Zhaoyan; Yang, Yuanming; Liu, Shanli
Abstract : Abstract: Several studies reported platelet-to-lymphocytes ratio (PLR), neutrophil-to-lymphocyte ratio (NLR) and red blood cell distribution width (RDW) were associated with the mid-term survival or cancer stage in pancreatic cancer. However, the relationship between these markers and the long-term prognosis of pancreatic cancer is still unknown. We investigated the relationship between PLR, NLR, RDW, and the long-term prognosis of pancreatic cancer. We included 182 pancreatic cancer patients who received operation at Linzi District People 's Hospital between August 2010 and January 2017. PLR, NLR, and RDW control data was obtained from 150 health volunteers from January 2011 to January 2017. Blood biochemical data before operation, preoperative computed tomography information, and pathological data of the pancreatic cancer patients were retrospectively collected for further analysis. Independent long-term prognostic significance of PLR, NLR, and RDW were analyzed in pancreatic cancer patients. PLR, NLR, and RDW were significantly increased in pancreatic cancer group compared with the control. Receiver operating characteristic (ROC) curve analysis showed the optimal cut-off values of PLR, NLR, and RDW were 150, 1.73, and 13.2 respectively. Overall survival (OS) analysis showed pancreatic cancer patients with PLR≥150 (median time, 24 vs 37.5 months, P =  .005) or RDW≥13.2 (median time, 27 months vs 37.5 months, P =  .018) had lower postoperative 5 year OS compared with pancreatic cancer patients with PLR<150 or RDW<13.2. Univariate and multivariable Cox regression analysis for postoperative 5 year OS data showed PLR≥150 (HR = 2.451, 95% CI 1.215–4.947; P =  .012) was still associated with the OS independently. Disease free survival (DFS) analysis showed pancreatic cancer patients with PLR≥150 (median time, 24 months vs 38 months, P =  .002) or RDW≥13.2 (median time, 24 months vs 37.5 months, P =  .006) had lower postoperative 5 year DFS compared with pancreatic cancer patients with PLR<150 or RDW<13.2. Univariate and multivariable Cox regression analysis for postoperative 5 year DFS data showed PLR≥150 (HR = 2.712, 95% CI 1.367–5.379; P =  .004) was independently associated with the DFS. In the present study, we find hematological biomarkers PLR≥150 is an independently predictive risk factor for the postoperative long-term prognosis in pancreatic cancer patients. Our study may provide a convenient way for the prognostic assessment of pancreatic cancer patients.